Case-Based fMRI Analysis after Cognitive Rehabilitation in MS: A Novel Approach - Hubacher, Martina; Kappos, Ludwig; Weier, Katrin; Stöcklin, Markus; Opwis, Klaus; Penner, Iris-Katharina (Frontiers in Neurology, 2015)
Background Cognitive decline in multiple sclerosis (MS) negatively impacts patients’ everyday functioning and quality of life. Since symptomatic pharmacological treatment is not yet available alternative treatment strategies such as cognitive rehabilitation are of particular interest. Objectives To analyse the ways in which MS patients respond to cognitive training, by combining behavioral and fMRI data in a case-based triangulation approach. Methods Ten relapsing-remitting (RR) MS patients aged between 39 and 58 years and between 1 and 8 years post MS diagnosis were included. EDSS ranged from 1 to 3.5. Participants had normal to high intelligence levels. Six patients were assigned to the training group (TG) and four to the control group (CG) without intervention. The TG received a 4-week computerized working memory (WM) training, consisting of 16 training sessions of 45 min duration each. Before and after the training a neuropsychological examination and fMRI investigation by using an N-back task of different complexity was applied. Results Patients in the TG responded differently to cognitive training. Four participants did not meet the triangulation criteria for being treatment responders. The two responders showed two distinct changes regarding activation patterns after training: (I) decreased brain activation associated with increased processing speed and (II) increased brain activation associated with higher processing speed and WM performance. Conclusion The occurrence of different and opposed response patterns after the same training indicates a risk in applying classical group statistics. Different and especially opposed patterns within the same sample may distort results of classical statistical comparisons. Thus, underlying processes may not be discovered and lead to misinterpretation of results.